2019
DOI: 10.33998/processor.2019.14.2.645
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Aplikasi Augmented Reality Pengenalan Tata Surya Berbasis Android Pada Sd Negeri 139/Iv Kota Jambi

Abstract: Metode pembelajaran di sekolah-sekolah saat ini masih dilakukan secara konvensional, menggunakan media seperti buku, papan tulis, dan alat peraga yang secara visual kurang menarik perhatian siswa sehingga berdampak pada rendahnya daya tangkap siswa terhadap materi yang disampaikan, salah satunya adalah materi pengenalan tata surya. Penelitian ini bertujuan untuk merancang perangkat ajar berbasis augmented reality sehingga objek akan terlihat lebih nyata dan meningkatkan pemahaman siswa sistem tata surya. Tahap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Research by Matin and Utomo [27] found that the use of AR applications can improve students' understanding. Furthermore, research by Prasetio, et al [26] used Unity 3D with Vuforia SDK to create an AR application to introduce the solar system. Vuforia SDK is used as a marker storage medium in the creation of AR [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Matin and Utomo [27] found that the use of AR applications can improve students' understanding. Furthermore, research by Prasetio, et al [26] used Unity 3D with Vuforia SDK to create an AR application to introduce the solar system. Vuforia SDK is used as a marker storage medium in the creation of AR [18].…”
Section: Resultsmentioning
confidence: 99%
“…None of them use markerless AR. Markers are used as markers for cameras that display 3D objects from the virtual world to the real world [26], [30]. The markers used to display 3D objects can be books integrated with AR [14], [33].…”
Section: Resultsmentioning
confidence: 99%
“…Detection at the beginning of the examination also shows the effectiveness of the intervention, in addition to providing services with an antenatal care standard, as known as 10T (Agustian et al, 2017 ), supporting examination services and doctor examination services at the primary health care which are carried out at least one time during pregnancy to carry out early detection of specific clinical conditions (Simbolon et al, 2020 ). 10T However, during the COVID-19 pandemic, examinations of pregnant women were carried out when they had complaints and experienced danger signs.…”
Section: Discussionmentioning
confidence: 99%
“…Tujuan dari penelitian ini adalah untuk merancang perangkat ajar berbasis augmented reality sehingga objek akan terlihat lebih nyata dan meningkatkan pemahaman siswa sistem tata surya. Hasil penelitian ini menghasilkan sebuah aplikasi augmented reality pengenalan tata surya berbasis android pada SD Negeri 139/IV Kota Jambi [4]. Penelitian lainnya yaitu berjudul Deskripsi Media Pembelajaran Yang Digunakan Guru Biologi Sma Negeri Di Kota Pontianak, Penelitian ini bertujuan untuk mengidentifikasi jenis media pembelajaran yang digunakan guru Biologi SMA Negeri di kota Pontianak.…”
Section: Pendahuluanunclassified